On rate-dependent dissipation effects in electro-elasticity - Saxena, Prashant; Vu, Duc Khoi; Steinmann, Paul (International Journal of Non-Linear Mechanics, 2014)
This paper deals with the mathematical modelling of large strain electro-viscoelastic deformations in electro-active polymers. Energy dissipation is assumed to occur due to mechanical viscoelasticity of the polymer as well as due to time-dependent effective polarisation of the material. Additive decomposition of the electric field E=Ee+Ev and multiplicative decomposition of the deformation gradient F=Fe Fv are proposed to model the internal dissipation mechanisms. The theory is illustrated with some numerical examples in the end. © 2014 Elsevier Ltd.
UnivIS-Import:2015-04-14:Pub.2014.tech.FT.FT-TM.onrate
Keywords: Electromechanical coupling; Non-linear electroelasticity; Rate dependence; Viscoelasticity